Stakeholder Interaction: A Qualitative Approach to Beach Tourism Management - Ristana Iswari Santosa, Davina; Nur Cahyani, Siti; Khairune Nisa, An Nuur (Ann Publisher, 2023)
This study aims to describe the natural tourism potential of three beaches in the Kanigoro Area.Each beach is managed individually by its respective beach pokdarwis, and its management has nointegration system. The Kanigoro community already has a relatively high level of tourism awareness, and there is a community of photographers who support tourism activities. However, this physical and non-physical potential must be managed effectively and efficiently to improve the welfare of the local Kanigoro community. This research uses descriptive qualitative methods to describe the situation orproblems in the Kanigoro Beach Area. This study allows researchers to understand the context in detail,analyze the variables involved, and explore the perceptions and views of relevant stakeholders.Diversification of tourism products plays a vital role in extending the level of tourist visits by encouragingthem to visit more than one beach to increase the tourism sector's economic benefits by increasing theduration of stay and tourist spending. Jargon